THE EFFECT OF SOCIAL MEDIA AND VIRAL MARKETING TOWARD PURCHASE DECISION AT SHOPEE - Inez Julieta Khasanah; Sudharto Prawata Hadi; Dinalestari Purbawati (Jurnal Ilmu Administrasi Bisnis, 2024)
Technology opens new channel namely E-commerce that allows its consumer to make purchase decisions through mobile phones. Shopee revenue reported to be fluctuated and decreased at the fourth quarter of  2021 to first quarter of 2022. The company also experienced an increase in losses in the first quarter of 2020, first quarter of 2021 and first quarter of 2022. This research aims to understand the effect of social media and viral marketing toward purchase decision at Shopee. This research uses quantitative data which use questionnaire from the sample of 100 Diponegoro University Students who use Shopee. This research is using non probability sampling and data analyzed using SPSS. The discussion resulted that the social media variable have positive significant influence on the purchase decision, the viral marketing variable have positive significant influence on the purchase decision, the social media and viral marketing variable simultaneously have positive significant influence on the purchase decision.  The company are recommend to increase the social media and viral marketing also for further research it is recommend to explore more about the respondent identity.Keywords: Purchase Decision; Social Media; Viral Marketing